The Beginners's guide to counseling and psychotherapy - Palmer, Stephen (Los Angeles, California : Sage, 2015)
This book is a guide to 26 different approaches to counselling and psychotherapy.
Part one : Psychodynamic approaches -- Part two : Cognitive behavioral approaches -- Part three : Humanistic-existential approaches -- Part four : Integrative and eclectic approaches -- Part five : Constructivist approaches -- Part six : Research and professional practice issues
Includes index.
Keywords: COUNSELING -- STUDY AND TEACHING